2012
DOI: 10.1089/thy.2011.0380
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib Enhances Docetaxel-Induced Apoptosis Through Inhibition of Nuclear Factor-κB Activation in Anaplastic Thyroid Carcinoma Cells

Abstract: Background: We previously reported the partial effectiveness of imatinib (also known as STI571, Glivec, or Gleevec) on anaplastic thyroid cancer (ATC) cells. Imatinib is a selective tyrosine kinase inhibitor that has been used for various types of cancer treatments. Recently, several reports have demonstrated that imatinib enhanced the sensitivity of cancer cells to other anticancer drugs. In this study, therefore, we investigated whether imatinib enhances the antitumor activity of docetaxel in ATC cells. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 39 publications
1
16
1
Order By: Relevance
“…Thus, D/D NPs are expected to effectively treat metastatic breast cancer, with evidence supporting the synergistic effects of the combination of DTX and DHA in treating metastatic breast cancer. In our study of the mechanism of D/D NPs in antimetastasis, we identied from previous research that DTX regulates the expression of NF-kB to inhibit cancer cell proliferation, 40 while DHA could also inuence the expression of NF-kB, via the AKT/NF-kB or NF-kB/GLUT1 pathway. 41 Our data suggested that the combination of DTX and DHA decreased the expression of NF-kB more than free DTX did.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, D/D NPs are expected to effectively treat metastatic breast cancer, with evidence supporting the synergistic effects of the combination of DTX and DHA in treating metastatic breast cancer. In our study of the mechanism of D/D NPs in antimetastasis, we identied from previous research that DTX regulates the expression of NF-kB to inhibit cancer cell proliferation, 40 while DHA could also inuence the expression of NF-kB, via the AKT/NF-kB or NF-kB/GLUT1 pathway. 41 Our data suggested that the combination of DTX and DHA decreased the expression of NF-kB more than free DTX did.…”
Section: Discussionmentioning
confidence: 99%
“…DTX is widely used as a cancer treatment (6)(7)(8)(9)(10)(11)(12)(13)(14). However, the emergence of chemotherapeutic resistance iTHs universal and DTX-resistance responses have been observed in a number of patients (15).…”
Section: Discussionmentioning
confidence: 99%
“…Docetaxel (DTX) is a well-established anti-mitotic chemotherapy agent that functions by interfering with cell division (5). It is used to treat a number of cancer types including metastatic or advanced breast, prostate, thyroid, gastric, ovarian and lung cancer based on its pro-apoptosis potential and its inhibitory effect on angiogenesis and cell viability (6)(7)(8)(9)(10)(11)(12)(13)(14). DTX has also been demonstrated to upregulate growth/differentiation factor 15 and results in chemoresistance in prostate cancer (15).…”
Section: Introductionmentioning
confidence: 99%
“…Another way of overcoming drug resistance mechanism and/or enhancing drug efficacy is the combination of TKIs or other target agents with chemotherapy or radiotherapy. In fact, it has been demonstrated that treatment with BEZ235 and paclitaxel, imatinib and docetaxel, and efatutazone, a PPARγ agonist, and paclitaxel have synergistic effects in vitro compared to the effect of treatment with a single agent (Copland et al 2006, Kim et al 2012. These combinations were demonstrated to be safe and tolerable in ATC patients in a phase 1 trial .…”
Section: Future Steps: Targeting Different Pathways and Combined Thermentioning
confidence: 99%